2020
DOI: 10.1063/5.0003592
|View full text |Cite
|
Sign up to set email alerts
|

Construction of microgrooves on the surface of alumina ceramic insulator to enhance its flashover strength

Abstract: The fabrication method of grooves on the surface of alumina and their influence on the surface flashover characteristics of the alumina insulator were studied in this paper. To prepare grooves with a regular surface structure, the UV laser was applied to carve grooves on the surface of alumina ceramic, and dilute hydrochloric acid was used to corrode and remove the residual materials produced in the laser carving process. By adjusting the laser parameters, periodic grooves were prepared on the surface of a cyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…14 Micropatterns on ceramic surfaces have been conducted by various techniques such as replication. 15 anodization, 16 hydrothermal methods, 17 soft lithography, 18 laser carving, [19][20][21] chemical etching, 22 or powder blasting with the help of PDMS mask. 23 Laser carving is especially useful for machining hard and/or brittle materials with high precision, excellent productivity, and surface quality.…”
Section: Introductionmentioning
confidence: 99%
“…14 Micropatterns on ceramic surfaces have been conducted by various techniques such as replication. 15 anodization, 16 hydrothermal methods, 17 soft lithography, 18 laser carving, [19][20][21] chemical etching, 22 or powder blasting with the help of PDMS mask. 23 Laser carving is especially useful for machining hard and/or brittle materials with high precision, excellent productivity, and surface quality.…”
Section: Introductionmentioning
confidence: 99%
“…Iwata's study showed that the surface flashover voltage in the direction perpendicular to the groove structure is approximately 1.2 times larger than that in the parallel direction under the AC voltage in a vacuum [17]. Liu and Huo et al, applied the fabrication method of microgrooves on the surface of alumina and polymer insulators, and found that the method can increase the flashover voltage significantly [18,19]. Cheng et al, studied the effect of periodically grooved dielectric on extending the flashover time lag in a vacuum, and ascribed the effect to the suppression of SEEA process [20].…”
Section: Introductionmentioning
confidence: 99%